Profile of Age, Gender, and Body Mass Index in Patient with Knee Osteoarthritis in Surabaya - Primadita Esther Rosita; Patricia Maria Kurniawati; Dwikora Novembri Utomo (Faculty of Medicine, Universitas Airlangga, 2021)
Background: Osteoarthritis is a degenerative disease which attacks all the joint parts, including articular cartilage, subchondral bone, ligament, meniscus, capsule, synovium, and periarticular tissue. Among various joints in human body, knee joint is the most affected by osteoarthritis. There are several established risk factors for knee osteoarthritis, including age, female gender, and obesity.Aim: This study aimed to describe age, gender, and body mass index (BMI) profile in knee osteoarthritis patients.Material and methods: This was a retrospective descriptive study with total sampling of 292 medical records of patient with knee osteoarthritis from Physical Medicine and Rehabilitation outpatient clinic, Universitas Airlangga Hospital, Surabaya.Results: Of all the data, there were 130 medical records included in this study. The majority characteristic of the subjects were older than 60 years old (54.6%), 98 (75.4%) were females and 32 (24.6%) were males. The highest male-female ratio was on 45-59 years old (1:4). Most patients were obese (58.5%) with the highest percentage was on 45-59 years old (51.3%).Conclusion: The majority of osteoarthritis patients in Universitas Airlangga Hospital Surabaya were elderly, females, and obese people.